2018
DOI: 10.3892/etm.2018.6417
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‑guided continuous fascia iliaca compartment block for pre‑operative pain control in very elderly patients with hip fracture: A randomized controlled trial

Abstract: The present study presented the results of a prospective, randomized controlled trial. The present study enrolled 98 very elderly patients with hip fractures, complicated with at least one cardiovascular, neurological or pulmonary disease, of whom 10 patients were excluded. A total of 88 patients were randomly assigned into 2 groups: i) The control group, receiving traditional analgesia including 50 mg Tramadol and 500 mg paracetamol orally three times a day from admission to surgery; and ii) the study group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In addition, 9 studies [ 25 , 30 , 40 44 , 46 , 49 ] were not designed as blinded. Although another 5 studies [ 24 , 29 , 36 , 39 , 50 ] were designed as blinded, they did not describe the blinding method in detail.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, 9 studies [ 25 , 30 , 40 44 , 46 , 49 ] were not designed as blinded. Although another 5 studies [ 24 , 29 , 36 , 39 , 50 ] were designed as blinded, they did not describe the blinding method in detail.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that FICB is nearly as effective for up to about 8 h after administration and can effectively control post-hip fracture pain, with a rapid onset. Later in 2018, Ma et al [ 29 ] evaluated the use of FICB in the very older adults (over 80 years) with hip fractures, with a traditional method (50 mg tramadol plus 500 mg paracetamol, orally, three times a day) set as controls. Outcomes revealed that the VAS pain scores under different phases in patients who had received FICB were significantly lower than those of the controls, including scores at rest and in the morning of the day of surgery, as well as passive movement scores at 1 h after analgesia at the time of admission and in the morning of the day of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent meta-analyses have suggested that efficiency of FICB and application approaches should be studied further ( 9 ). It has been suggested that continuous FICB performed using a conventional technique provides better pain control than patient-controlled analgesia (PCA) in elderly patients ( 10 ). To the best of our knowledge, no study in the current literature has evaluated the effect of the suprainguinal technique, especially in the elderly population.…”
Section: Introductionmentioning
confidence: 99%